2021
DOI: 10.1016/j.celrep.2021.109276
|View full text |Cite
|
Sign up to set email alerts
|

BMPR-2 gates activity-dependent stabilization of primary dendrites during mitral cell remodeling

Abstract: Developing neurons initially form excessive neurites and then remodel them based on molecular cues and neuronal activity. Developing mitral cells in the olfactory bulb initially extend multiple primary dendrites. They then stabilize single primary dendrites while eliminating others. However, the mechanisms underlying selective dendrite remodeling remain elusive. Using CRISPR-Cas9-based knockout screening combined with in utero electroporation, we identify BMPR-2 as a key regulator for selective dendrite stabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 64 publications
0
22
0
Order By: Relevance
“…Previous studies indicated that various types of Rho GTPases regulate activity-dependent dendrite morphogenesis, including growth and retraction (Li et al, 2002; Luo, 2000; Murakoshi et al, 2011; Sin et al, 2002). Using CRISPR-Cas9-based screening in mitral cells (Aihara et al, 2021), we found that Rho subfamily GTPases are required for dendrite pruning (Figure 4H). When all of the Rho subfamily GTPases (RhoA, RhoB, and RhoC) were knocked out in mitral cells (RhoABC TKO), dendrite pruning was prevented.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies indicated that various types of Rho GTPases regulate activity-dependent dendrite morphogenesis, including growth and retraction (Li et al, 2002; Luo, 2000; Murakoshi et al, 2011; Sin et al, 2002). Using CRISPR-Cas9-based screening in mitral cells (Aihara et al, 2021), we found that Rho subfamily GTPases are required for dendrite pruning (Figure 4H). When all of the Rho subfamily GTPases (RhoA, RhoB, and RhoC) were knocked out in mitral cells (RhoABC TKO), dendrite pruning was prevented.…”
Section: Resultsmentioning
confidence: 99%
“…The subsequent depolarization induces the neuron-wide activation of RhoA, leading to the pruning of non-protected dendrites (lateral inhibition). NMDAR-dependent local signals also activate Rac1 to stabilize the dendrite (Aihara et al ., 2021). Scale bars, 20 μm in (A) and (C) left; 5 μm in (C) right.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence for signalling pathways that distinguish 'to-be-pruned' versus 'to-be-stabilised' dendrites remains a key target for the near future. However, permissive regulators of this process have been recently identified (Aihara et al, 2021), and there is a strong link between OSN-driven dendrite stabilisation and activity-dependent strengthening of OSN-to-M/TC synaptic connections (Inoue et al, 2018(Inoue et al, , 2021.…”
Section: Astrocytesmentioning
confidence: 99%